Neurofibromatosis‐1 gene deletions and mutations in de novo adult acute myeloid leukemia. Issue 4 (5th March 2013) - Boudry‐Labis, Elise; Roche‐Lestienne, Catherine; Nibourel, Olivier; Boissel, Nicolas; Terre, Christine; Perot, Christine; Eclache, Virginie; Gachard, Nathalie; Tigaud, Isabelle; Plessis, Ghislaine; Cuccuini, Wendy; Geffroy, Sandrine; et al.
<x xml:space="preserve">Abstract</x> Germline heterozygous alterations of the tumor‐suppressor gene neurofibromatosis‐1 (NF1) lead to neurofibromatosis type 1, a genetic disorder characterized by a higher risk to develop juvenile myelomonocytic leukemia and/or acute myeloid leukemia (AML). More recently, somatic 17q11 deletions encompassing NF1 have been described in many adult myeloid malignancies. In this context, we aimed to define NF1 involvement in AML. We screened a total of 488 previously untreated de novo AML patients for the NF1 deletion using either array comparative genomic hybridization (aCGH) or real‐time quantitative PCR/fluorescence in situ hybridization approaches. We also applied massively parallel sequencing for in depth mutation analysis of NF1 in 20 patients including five NF1‐deleted patients. We defined a small ∼0.3 Mb minimal deleted region involving NF1 by aCGH and an overall frequency of NF1 deletion of 3.5% (17/485). NF1 deletion is significantly associated with unfavorable cytogenetics and with monosomal karyotype notably. We discovered six NF1 variants of unknown significance in 7/20 patients of which only one out of four disappeared in corresponding complete remission sample. In addition, only one out of five NF1‐deleted patients has an acquired coding mutation in the remaining allele. In conclusion, direct NF1 inactivation is infrequent in de novo AML and may be a secondary event probably involved in leukemic progression. Am. J. Hematol. 88:306–311, 2013. © 2013 Wiley Periodicals, Inc.